Stent and triple stent accommodation in aorta anomaly and length change. Case study - Garcia del Pino, Gilberto; de Almeida Costa, Cleinaldo; Benjamin Brandão Pitta, Guilherme; Dantas dos Santos, Marcos; Costa, Nilton; Torres, Aristide Rivera (Seven Editora, 2023)
To improve public health, multidisciplinary teams of  engineers and physicians work in various medical [1-3] and materials sectors in the development of new biomedical materials such as prostheses [4-5], as well as medical instruments [6] and development of technologies to improve the level of lives of patients who need these devices and solutions for different diseases.DOI: https://doi.org/10.56238/devopinterscie-170